Chapter Promozione del senso di appartenenza alla scuola ed ospedalizzazione pediatrica. Qual è il ruolo delle associazioni nella regione Toscana? - Tomberli, Lucrezia (Studies on Adult Learning and Education, 2022)
Several associations in Italy are involved in pediatric disease and support for children and adolescents in conditions of medical complexity, with Tuscany boasting a territory particularly committed to social issues. This study aims to understand if currently in Tuscany there are associations engaged in promoting the sense of school belonging of the student with pathology. In order to achieve this objective, Tuscan associations have been mapped using five different mapping methods. Only one association was found through this mapping. The psychologist at the association was interviewed to understand the point of view of the association on this topic.